2016
DOI: 10.5812/ijhrba.35057
|View full text |Cite
|
Sign up to set email alerts
|

Study of Oxidants and Antioxidants in Addicts

Abstract: Context: This study was a systematic review that aimed to extract published articles regarding oxidant and antioxidants status in opium addiction by searching in PubMed, Google Scholar engine, SID, and Magiran databases. Evidence Acquisition: Sixty-six published articles were investigated in this review, which were selected from studies among the Iranian society and other societies from 1976 to 2015. All articles published in different fields of descriptive-analytical, experimental, and interventional studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…It should always be taken into consideration that recovering from any substance use disorder (SUD) does not only involve changes in the diet but also gaining information and knowledge, increasing self-awareness, developing skills for sober living, and following a structured program of change. Several studies have also shown the benefits of nutrition services in the treatment outcomes when incorporated in the rehabilitation program, which includes sobriety success rate, positive behavior change, healthier food choices, decrease in BMI, and reduced waist circumference (16)(17)(18)(19). In another study, lower levels of circulating leptin, coupled with a diet high in fat and carbohydrates, caused a metabolic imbalance among cocaine-dependent males, resulting in excessive weight gain throughout rehabilitation (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should always be taken into consideration that recovering from any substance use disorder (SUD) does not only involve changes in the diet but also gaining information and knowledge, increasing self-awareness, developing skills for sober living, and following a structured program of change. Several studies have also shown the benefits of nutrition services in the treatment outcomes when incorporated in the rehabilitation program, which includes sobriety success rate, positive behavior change, healthier food choices, decrease in BMI, and reduced waist circumference (16)(17)(18)(19). In another study, lower levels of circulating leptin, coupled with a diet high in fat and carbohydrates, caused a metabolic imbalance among cocaine-dependent males, resulting in excessive weight gain throughout rehabilitation (20).…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of nutrient-dense foods and antioxidants was known to aid in reducing inflammation and cell oxidation and providing adequate nourishment to the body. A systematic review showed that among opium users, there was an increase in the production of free radicals and reactive oxygen species, a decrease in the concentration of vitamins A, E, C, and total antioxidant capacity, and a decrease in the activities of an enzymatic and non-enzymatic oxidant such as glutathione and glutathione peroxidase, superoxide dismutase and catalase (16). Unfortunately, there was an increase in the percentage of overweight and obesity at the end of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Signi cantly higher MDA content was detected in RBCs of the addicted group, although the same has not been found consistently in plasma samples. Higher MDA content in the RBCs reveals an important clue for oxidative damage in the nicotine-addicted respondents [39]. SOD is a well-known primary antioxidant enzyme that counteracts superoxide radicals produced in the cells, serves as a powerful defensive system of cells [40].…”
Section: Discussionmentioning
confidence: 99%
“…A questionnaire of 10 items based on the frequency of emotional feelings and thoughts during the past month was given to volunteers and asked them to respond. According to the overall individual's score, all volunteers were categorized into three stress categories as low stress (<13), moderate stress (14-26), and high stress (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) [30].…”
Section: Psychological Assessmentmentioning
confidence: 99%
“…On the other hand, Koç et al, (2015) indicated that SOD can react with produced free radicals as the first antioxidant enzyme, resulting SOD activity become high to destroying existed free radicals. Moreover, cells can grow to advancement of their antioxidant enzymes including SOD, catalase (CAT) and glutathione-S-transferase (GST) to keep away from adverse effects of free radicals (Karajibani et al, 2017). The intermediate dose of P. farcta extract significantly reduced the elevation of MDA in EG treated rats, also low and intermediate doses non-significantly reduced the effects of EG on SOD activity.…”
Section: Discussionmentioning
confidence: 99%